2023
DOI: 10.1038/s41598-023-38593-w
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive norms caused increases in mask wearing during the COVID-19 pandemic

Abstract: Human sociality is governed by two types of social norms: injunctive norms, which prescribe what people ought to do, and descriptive norms, which reflect what people actually do. The process by which these norms emerge and their causal influences on cooperative behavior over time are not well understood. Here, we study these questions through social norms influencing mask wearing during the COVID-19 pandemic. Leveraging 2 years of data from the United States (18 time points; n = 915), we tracked mask wearing a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Social norm messaging had been successfully employed in encouraging pandemic health behavior such as hand sanitizer use ( Mobekk and Stokke, 2020 ) and increasing vaccination rates ( Zhang and Jin, 2023 ). For the specific behavior of mask wearing, a longitudinal study found that social norms were important determinants of mask wearing behavior (with descriptive norms being more influential than injunctive norms) ( Heiman et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Social norm messaging had been successfully employed in encouraging pandemic health behavior such as hand sanitizer use ( Mobekk and Stokke, 2020 ) and increasing vaccination rates ( Zhang and Jin, 2023 ). For the specific behavior of mask wearing, a longitudinal study found that social norms were important determinants of mask wearing behavior (with descriptive norms being more influential than injunctive norms) ( Heiman et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…The SARS-COV-2 pandemic has also drawn attention to the social norm component of preventive behaviour, where social norms can be either enforced through social interactions within groups of individuals sharing a common social space (social group (i)) and sustained by feelings of anxiety, guilt, embarrassment or shame if violated 27 , 28 , or defined by the most common and expected behaviour from the social group (ii). In the context of SARS-COV-2, it has been highlighted that social norms are constitutive of compliance with preventive measures 29 32 . We argue that social norms also apply to VBDs’ preventive behaviour.…”
Section: Introductionmentioning
confidence: 99%